Design of a Raw Material Warehouse Layout Utilizing The Class-Based Storage Method For the Textile and Textile Products Industry - Desiawan, Victor Assani; Octavia, Lia Nur; Sulistiyo, Eko; Firmansyah, Fariz; Apsari, Risha Firly (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2024)
The COVID-19 pandemic has caused competition in the industrial sector to become increasingly fierce. So entrepreneurs in the induction sector must create new strategies to maximize company support facilities. One of the company's supporting facilities is a warehouse. Entrepreneurs can benefit from the proposed raw materials warehouse layout design by utilising the Class-Based Storage Method. This method facilitates the retrieval of raw materials and offers a streamlined process. This Method procedure comprises several stages: counting the number of pallets stored in a warehouse that is 191 pallets, determine the hallway and the dimensions of the warehouse, storage media with algorithms determine the depth of the line and allocate floor space with Larson algorithm. We receive a suggested design for the raw materials warehouse plan, including the storage area size of 148.32 m2, total distance moved out of the entire feedstock is 1727.65m with a total Material Handling costs for raw materials is Rp 600,289.